2019
DOI: 10.1111/cobi.13307
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term declines of European insectivorous bird populations and potential causes

Abstract: Evidence of declines in insect populations has recently received considerable scientific and societal attention. However, the lack of long‐term insect monitoring makes it difficult to assess whether declines are geographically widespread. By contrast, bird populations are well monitored and often used as indicators of environmental change. We compared the population trends of European insectivorous birds with those of other birds to assess whether patterns in bird population trends were consistent with decline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
179
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(189 citation statements)
references
References 43 publications
6
179
1
3
Order By: Relevance
“…The y axis was truncated at the lower limit to allow better visualization of patterns across latitude (excluding seven and three traps with very low number of species and individuals in the NB zone, respectively) [Colour figure can be viewed at wileyonlinelibrary.com] and affect ecosystems services. Specifically, declines in insect abundance (regardless of their causes) appearto drive declines in bird population trends, with pronounced effects on insectivores and long-distance migrant species(Bowler, Heldbjerg, Fox, Jong, & Böhning-Gaese, 2019;Hallmann, Foppen, Turnhout, Kroon, & Jongejans, 2014).Our results highlight that changes in richness and abundance can be decoupled from each other(Schipper et al, 2016). In a similar vein,Antão et al (2019) reported how temperature-related trends in the number of individuals and number of species were not only decoupled, but exhibited geographically contrasting patterns during several decades of climate change.…”
supporting
confidence: 54%
“…The y axis was truncated at the lower limit to allow better visualization of patterns across latitude (excluding seven and three traps with very low number of species and individuals in the NB zone, respectively) [Colour figure can be viewed at wileyonlinelibrary.com] and affect ecosystems services. Specifically, declines in insect abundance (regardless of their causes) appearto drive declines in bird population trends, with pronounced effects on insectivores and long-distance migrant species(Bowler, Heldbjerg, Fox, Jong, & Böhning-Gaese, 2019;Hallmann, Foppen, Turnhout, Kroon, & Jongejans, 2014).Our results highlight that changes in richness and abundance can be decoupled from each other(Schipper et al, 2016). In a similar vein,Antão et al (2019) reported how temperature-related trends in the number of individuals and number of species were not only decoupled, but exhibited geographically contrasting patterns during several decades of climate change.…”
supporting
confidence: 54%
“…Bowler et al . () showed that declines in insectivorous birds was most strongly felt in agricultural habitats, particularly grasslands, that caused bird communities to be dominated by diet generalists. On the North American continent, similar patterns are apparent (Fitzgerald et al ., ; Michel et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…Our results might be showing the serious consequences of current low insectivorous bird densities on the pest control ecosystem service carried out in olive orchards. Since alarming bird declines have been reported in North America (Rosenberg et al, 2019) and Europe in the last decades (Bowler, Heldbjerg, Fox, de Jong, & Böhning-Gaese, 2019; Inger et al, 2015), avian insectivory function in olive orchards is expected to be aggravated in the olive farms in the near future, since olive matrix is clearly suboptimal for avian insectivores, and suboptimal habitats become empty earlier that optimal ones. According to our results, urgent actions should be taken to reverse this situation, such as policy changes aimed to the recuperation of landscape heterogeneity and semi-natural patches in landscapes homogenized by monoculture, and active restoration of bird assemblages (e.g.…”
Section: Resultsmentioning
confidence: 99%